Improving alignment between Business and IT departments: towards an effective Enterprise Architecture and its role within the corporate organisation - Kariem, Latiefa (Department of Information Systems, 2023)
While it is widely acknowledged that alignment between Business and IT is important to remain competitive and for improving business performance, achieving, and maintaining alignment between IT and Business divisions is not always easy. While there are many ways to improve Business IT Alignment, a mature Enterprise Architecture has been proven as a contributor to Business and IT Alignment due to its holistic approach to considering all aspects from a technical and organisational perspective (Kurnia et.al, 2020). Other factors which are believed to improve Business IT Alignment culture, structure, communication, and strategy, to name a few. To the researcher's knowledge, not many studies have considered how these four factors, together with Enterprise Architecture fit together harmoniously to create, contribute to, and maintain strategic alignment between Business and IT divisions in a single organisation. This dissertation seeks to fill this gap by establishing which of these four variables contribute to improving alignment between Business and IT and if Enterprise Architecture has a role to play in achieving it. A conceptual model derived from the literature review guides this research through applying a moderation approach to determine if a balance in alignment can be achieved. This research is an empirical study conducted by an insider of Company A which followed a single organisation survey approach with 40 respondents at a South African Oil and Gas Company. It follows an objectivism ontology, with a positivist philosophical approach as an epistemology. A mixed method approach was followed for data collection, and data analyses was done using quantitative methods. Six hypotheses are presented of which two of the six hypotheses are rejected based on Regression Analysis testing. The key findings present that even though Enterprise Architecture and its' benefits appear to be largely understood at Company A, both maturity levels of business-IT alignment and Enterprise Architecture is relatively low so there are indeed opportunities for improving both maturity levels. While literature often indicates that Culture, Communication, Structure and Strategy have been identified as key enablers of BITA, the researcher only proved that two variables, Communication and Strategy has a significant effect of BITA. After establishing BITA and EA Maturity levels, provides recommendations for improving EA maturity and motivates how these improvements, if implemented, can strengthen alignment between business and IT so that EA can enable better alignment between Business and IT at Company A. These findings can support the existing EA and BITA body of knowledge in two ways: 1. As a case which proved that not all 4 common variables necessarily have a significant effect on BITA, 2, provides practical and implementable opportunities for improving EA at an organisation where its benefits is already understood.